Peran Guru dalam Mengembangkan Kecerdasan Emosional Anak Usia Dini di SDIT Alam Nurul Islam 2 Ngawi - Reza Zanjabila; Agus Budiman (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to determine the role of teachers in developing early childhood emotional intelligence in Alam Nurul Islam 2 Ngawi Integrated Islamic Elementary School (SDIT). These researchers draw on the theory of psychologist Daniel Goleman, who argues that emotional intelligence is more important than intellectual intelligence. This study used qualitative research with observational data collection techniques, interviews, and documentation. The results of the data analysis are presented descriptively. The conclusion drawn from this study is that the role of teachers is very important in developing children's emotional intelligence, which includes 5 aspects as expressed by Daniel Golema,n including the role of teachers in building the ability to recognize children's emotions, building the ability to manage children's emotions, building children's self-motivation abilities, building children's empathy abilitiesand, and fostering relationships with others. The results of this study can be concluded that the role of teachers at SDIT Alam Nurul Islam 2 Ngawi has applied 5 aspects in developing early childhood emotional intelligence well.   Keywords: Teacher Role, Emotional Intelligence, Early Childhood